Secondary cytolytic T lymphocyte stimulation by purified H-2Kk in liposomes. - Herrmann, S H (1981)
Purified H-2Kk incorporated into lipid vesicles induced a secondary allogeneic cytolytic T lymphocyte response. However, the level of the response was much less than that generated by using purified plasma membranes containing an equivalent amount of antigen. Similarly, reconstituted membranes stimulated less effectively than did intact plasma membranes. In both cases the stimulating activity of the antigen was increased by including a detergent-insoluble membrane matrix fraction during formation of the liposomes or reconstructed vesicles. Liposomes formed in the presence of the matrix were larger, were more irregular in shape, and had a higher density than those formed in its absence. Both the H-2 antigen and matrix proteins were incorporated into the same vesicles. The greater antigenicity of H-2 in vesicles containing the matrix protein might be due to either the larger size of the liposomes or interaction of the antigen with a component(s) of the matrix.